Positive electrode material, preparation method thereof, positive electrode sheet and sodium ion battery
Patent Information
- Application Number
- CN202510570043.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-04-30
AI Technical Summary
[0003]本发明的主要目的是提出一种正极材料及其制备方法、正极极片和钠离子电池,旨在改善钠基层状氧化物正极材料循环性能差的问题
[0019]本发明实施例还提出一种钠离子电池,所述钠离子电池包括上述的正极极片。
Smart Images

Figure CN120453331B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and in particular to a positive electrode material and its preparation method, a positive electrode sheet, and a sodium-ion battery. Background Technology
[0002] In sodium-ion batteries, layered oxide cathode materials (such as NaXMeO2) have become a research hotspot due to their excellent ion transport channels and high theoretical specific capacity. However, these materials generally suffer from large volume changes and significant particle expansion or contraction during cycling, leading to particle breakage or pulverization, which significantly affects cycle stability. Therefore, there is an urgent need to develop a novel sodium-ion battery cathode material that can reduce volume changes and improve cycle stability through morphology control. Summary of the Invention
[0003] The main objective of this invention is to propose a cathode material and its preparation method, a cathode electrode sheet, and a sodium-ion battery, aiming to improve the poor cycle performance of sodium-based crystalline oxide cathode materials.
[0004] To achieve the above objectives, this invention provides a cathode material, which is a sodium-based crystalline oxide comprising an outer coating layer and a core agglomerate. The core agglomerate is embedded within the outer coating layer, and the outer coating layer at least partially covers the core agglomerate. The outer coating layer is formed by stacking sheet-like primary particles, and the core agglomerate is formed by interweaving and agglomerating granular primary particles. The average specific surface area of the sheet-like primary particles is smaller than the average specific surface area of the granular primary particles.
[0005] In some embodiments, the average specific surface area of the sheet-like primary particles is S1, the average specific surface area of the granular primary particles is S2, and the ratio of S1 to S2 is greater than 0 and less than or equal to 0.1.
[0006] In some embodiments, the average specific surface area S1 of the plate-like primary particles is 0.2 m². 2 / g~0.5m 2 / g; and / or, the average specific surface area S2 of the granular primary particles is 1m². 2 / g~10m 2 / g.
[0007] In some embodiments, the average length L of the sheet-like primary particles is 1.5 μm to 10 μm, and the average width W is 0.5 μm to 8 μm; and / or, the average particle size R of the granular primary particles is 0.1 μm to 2 μm.
[0008] In some embodiments, the chemical formula of the positive electrode material is Na. x Ni aFe b Mn c M d O2, wherein (a+b+c+d)=1, 0.6≤x≤1.0, 0.1≤a≤0.4, 0.1≤b≤0.4, 0.2≤c≤0.8, 0.01≤d≤0.2; M is selected from at least one element from K, Li, Ca, Cu, Mg, Zn, Sr, B, Y, Sn, Al, Nb, Ti, Zr, W, Sr, Co, Mo; and / or, the average particle size Dv50 of the cathode material is 6μm~15μm.
[0009] This invention also proposes a method for preparing a cathode material, comprising the following steps:
[0010] A metal salt solution containing nickel, iron, and manganese sources is prepared. The metal salt solution is then subjected to a co-precipitation reaction to obtain a precursor. The precursor is mixed with sodium and M sources and subjected to a first calcination treatment to obtain a cathode material precursor. The cathode material precursor is then reacted with M... 1 The source is mixed and then subjected to a second calcination treatment to obtain the cathode material;
[0011] Alternatively, a metal salt solution containing a nickel source, an iron source, a manganese source, and an M source is prepared, and the metal salt solution is subjected to a co-precipitation reaction to obtain a precursor; the precursor is mixed with a sodium source and subjected to a first sintering treatment to obtain a cathode material precursor; the cathode material precursor is then mixed with M... 1 After mixing the source materials, a second sintering process is performed to obtain the cathode material.
[0012] The M source includes at least one of the following: K source, Li source, Ca source, Cu source, Mg source, Zn source, Sr source, B source, Y source, Sn source, Al source, Nb source, Ti source, Zr source, W source, Sr source, Co source, and Mo source.
[0013] The M 1 The source includes at least one of Cu, B, Nb, W, Ti, and Ca sources; the M 1 The particle size distribution of the source is 2≤(D90-D10) / D50≤10.
[0014] In some implementations, the M 1 The particle size parameters of the source are 0.1μm≤D10≤2μm, 10μm≤D90≤100μm, and 0.8μm≤D50≤10μm;
[0015] And / or, the M 1 The mass ratio of the source to the cathode material precursor is 1:(20-200);
[0016] And / or, the molar ratio of sodium in the sodium source to nickel in the nickel source, iron in the iron source, manganese in the manganese source, and M in the M source is (0.6-1):(0.1-0.4):(0.1-0.4):(0.2-0.8):(0.01-0.2).
[0017] In some embodiments, the first sintering treatment lasts for 3 to 12 hours and the calcination temperature is 800°C to 950°C; and / or, the second sintering treatment lasts for 6 to 15 hours and the calcination temperature is 850°C to 1000°C.
[0018] The present invention also proposes a positive electrode sheet, comprising a current collector and a positive electrode active material layer disposed on at least one surface of the current collector, wherein the positive electrode active material layer comprises the above-mentioned positive electrode material or a positive electrode material prepared by the above-mentioned preparation method.
[0019] This invention also proposes a sodium-ion battery, which includes the above-described positive electrode sheet.
[0020] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0021] The cathode material in this invention exhibits a microscopic morphology resembling a "meat sandwich," meaning that a single secondary agglomerate of the cathode material consists of several sheet-like primary particles and a core agglomerate, with the core agglomerate embedded and clustered between larger sheet-like particles. In this particle morphology, these sheet-like particles, through their sheet-like shape and stacking pattern, form a stable framework structure within the material, primarily limiting the volume expansion of the core agglomerate. Simultaneously, they also disperse the stress generated during charging and discharging, preventing structural damage caused by volume changes. The core agglomerate, composed of interwoven smaller primary particles, possesses a high specific surface area and becomes the main active component of the material, undertaking most of the electrochemical reaction tasks. These small particle agglomerates are encapsulated and fixed by the larger sheet-like particles, thus being constrained during charging and discharging, significantly reducing volume expansion and stress accumulation.
[0022] Through the above design, large, sheet-like particles firmly "clamp" the small particle agglomerates in the middle, which not only effectively limits the volume change of the small particle agglomerates during cycling, but also significantly alleviates the stress between the small particles. This synergistic mechanism improves the cycling stability of the material and solves the problem of rapid performance degradation of traditional sodium-based layered oxide cathode materials during long-term cycling.
[0023] The method for preparing the cathode material of the present invention involves adding M, which has a wide particle size distribution, during the second sintering process. 1The source powder acts as a fluxing agent, achieving uneven fluxing on the particles, thereby enabling the simultaneous existence of large flaky particles and small particle agglomerates within the same particle. Attached Figure Description
[0024] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.
[0025] Figure 1 This is a SEM image of the cathode material of Embodiment 1 of the present invention.
[0026] Figure 2 This is a SEM image of the cathode material of Comparative Example 1 of the present invention.
[0027] Figure 3 This is a SEM image of the cathode material of Comparative Example 2 of the present invention.
[0028] Figure 4 This is a SEM image of the cathode material of Comparative Example 3 of the present invention.
[0029] The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0030] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0031] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a specific parameter, it is expected that ranges of 60-110 and 80-120 are also included. Furthermore, if minimum range values of 1 and 2 are listed, and if maximum range values of 3, 4, and 5 are listed, then the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this application, unless otherwise stated, the numerical range "ab" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed in this article; "0-5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0032] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.
[0033] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.
[0034] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.
[0035] In this application, the term "average specific surface area" is defined as the total surface area per unit mass of particles (m²). 2 The specific surface area of the particles was determined using nitrogen adsorption. At least three independent tests were performed for each particle type, and the arithmetic mean of these test results was calculated as the average specific surface area for that particle type.
[0036] The terms "average length L" and "average width W" are used to describe the geometric dimensional characteristics of plate-like primary particles. "Average length L" is defined as the dimension of the plate-like particle along its longest direction, while "average width W" is defined as the lateral dimension perpendicular to the length direction. The method for calculating these dimensions involves taking morphological images of the particles using a scanning electron microscope, randomly selecting at least 50 particles from the images, and measuring the length and width of each particle using software tools such as ImageJ. Finally, the arithmetic mean of all measurement data is calculated to determine the average length L and average width W of the particles.
[0037] The term "average particle size R" refers to the equivalent spherical diameter of granular primary particles. It can be calculated using a Malvern 3000 instrument, which measures particle size distribution based on the principle of dynamic light scattering and directly provides the Dv50 value, i.e., the volume median particle size. At least 100 particles are randomly selected for measurement, and the arithmetic mean of their diameters is calculated to determine the average particle size R.
[0038] Sodium-based oxides are a class of substances that contain sodium ions (Na+). + Na+ is a layered cathode material with charge carriers and is widely used in sodium-ion batteries. These materials typically have the general formula Na+. x TMO2 (where x represents the sodium ion content, and TM represents a transition metal element, such as Mn, Fe, Co, Ni, etc.). Due to its unique crystal structure and properties, sodium-based layered oxide cathode materials exhibit the following advantages in sodium-ion batteries: sodium resources are abundant and inexpensive, making them more economical than lithium-ion batteries; the transition metal oxide layer provides abundant active sites, enabling higher theoretical specific capacity, thus meeting the demands of high-performance energy storage. However, these materials also present some challenges. During charge and discharge, the repeated insertion and extraction of sodium ions leads to significant volume expansion and contraction of the cathode material. This volume change triggers the accumulation of internal stress, resulting in particle breakage, pulverization, or structural collapse, thereby affecting the material's structural stability and cycle life.
[0039] Based on this, this invention proposes a cathode material, which is a sodium-based crystalline oxide, comprising an outer coating layer and a core agglomerate. The core agglomerate is embedded inside the outer coating layer, and the outer coating layer at least partially covers the core agglomerate. The outer coating layer is formed by stacking sheet-like primary particles, and the core agglomerate is formed by interweaving and agglomerating granular primary particles. The average specific surface area of the sheet-like primary particles is smaller than that of the granular primary particles.
[0040] Please see Figure 1In one embodiment of the present invention, the positive electrode material consists of two parts—an outer coating layer and a core agglomerate. The core agglomerate is embedded within the outer coating layer, and the outer coating layer at least partially covers the core agglomerate. This structure is similar to a "roujiamo" (Chinese hamburger), with the outer coating layer acting as the "bread" and the core agglomerate as the "meat." The outer coating layer is composed of stacked sheet-like primary particles. These sheet-like primary particles have a relatively large average length, forming a relatively stable framework structure that provides support and protection. The core agglomerate is composed of smaller, interwoven, and aggregated granular primary particles. These granular primary particles have a small average particle size and a high specific surface area, and are the main active part of the material, responsible for participating in electrochemical reactions. The large sheet-like particles mainly limit the volume expansion of the core agglomerate, while also dispersing the stress generated during charging and discharging, protecting the core agglomerate from mechanical damage. The core agglomerate, composed of small particles, is the main active part of the material, undertaking most of the electrochemical reaction tasks. Because it is fixed by the outer coating layer, volume changes and stress accumulation can be reduced.
[0041] The technical solution of this invention not only optimizes the mechanical stability and electrochemical performance of the material by adopting this design, but also solves the performance degradation problem caused by volume expansion and stress accumulation in traditional sodium-based layered oxide cathode materials during cycling.
[0042] In some embodiments, the average specific surface area of the plate-like primary particles is S1, and the average specific surface area of the granular primary particles is S2, where the ratio of S1 to S2 is greater than 0 and less than or equal to 0.1. Specific surface area refers to the total surface area per unit mass of material; a larger specific surface area indicates more active sites on the material surface. S1 / S2 ≤ 0.1 indicates that the specific surface area of the plate-like primary particles is much smaller than that of the granular primary particles. Due to their larger size and lower specific surface area, plate-like particles exhibit lower activity in electrochemical reactions. They mainly serve a mechanical support role, forming a stable framework structure and limiting the volume expansion of the core aggregates during charge and discharge. Granular particles, with their higher specific surface area, provide more active sites and undertake most of the electrochemical reaction tasks. This allows the material to achieve higher capacity utilization during charge and discharge. By rationally designing the specific surface area ratio of plate-like and granular primary particles, an optimal balance can be found between structural stability and electrochemical performance. Plate-like particles provide mechanical support, while granular particles contribute the main electrochemical activity; together, they work synergistically to improve the overall performance of the material.
[0043] In some embodiments, the average specific surface area S1 of the plate-like primary particles is 0.2 m². 2 / g~0.5m 2 / g. Large, flaky primary particles typically have a smaller specific surface area due to their larger size.
[0044] In some embodiments, the average specific surface area S2 of the granular primary particles is 1m². 2 / g~10m 2 / g. Specific surface area refers to the total surface area per unit mass of material (unit: m²). 2 / g). For cathode materials, specific surface area directly affects their contact area with the electrolyte, thus influencing the electrochemical reaction. Particulate primary particles have a higher specific surface area, providing more active sites.
[0045] In some embodiments, the average length L of the plate-like primary particles is 1.5 μm to 10 μm, and the average width W is 0.5 μm to 8 μm. The length and width can be directly measured by observing the morphology of the plate-like particles using a scanning electron microscope or similar instrument. A plate-like primary particle is a particle with a flattened morphology, and its geometry can be described by its length and width. "Average length" refers to the main dimension of the plate-like particle in its extension direction. The average length L of the plate-like primary particles is between 1.5 μm and 10 μm. As examples, the average length L can be typical but not limiting values such as 1.5 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm. A longer length contributes to the formation of a more stable stacked structure, thereby enhancing the mechanical strength of the outer coating layer and its confinement of the core agglomerates. The average width W of the plate-like primary particles is between 0.5 μm and 8 μm. As an example, the average width W can be a typical but not limited value, such as 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, or 8μm. Width and length together determine the planar area of the sheet-like particles; a larger area allows for better coverage and protection of the core aggregates. Sheet-like primary particles with the aforementioned size range can better form an outer coating layer and provide mechanical support for the core aggregates. A larger length and moderate width enable these particles to form a stable framework structure when stacked.
[0046] In some embodiments, the average particle size R of the granular primary particles is 0.1 μm to 2 μm. Here, "particle size" refers to the equivalent diameter of the particle (e.g., the diameter when the particle is spherical), used to describe the size of the particle. The morphology of the granular primary particles can be rod-shaped, spherical, quasi-spherical, plate-shaped, linear, etc. As examples, the average particle size R can be typical but not limiting values such as 0.1 μm, 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, and 2 μm. Within the above particle size range, the granular primary particles have a relatively small and moderate particle size, which can provide a large specific surface area, thereby increasing the active sites for electrochemical reactions and improving the specific capacity and rate performance of the material. This moderate size range helps to achieve a balance between high specific surface area and good structural stability.
[0047] In some implementations, the chemical formula of the cathode material is Na. x Ni a Fe b Mn c M d O2, where (a+b+c+d)=1, 0.6≤x≤1.0, 0.1≤a≤0.4, 0.1≤b≤0.4, 0.2≤c≤0.8, 0.01≤d≤0.2; M is selected from at least one of the elements K, Li, Ca, Cu, Mg, Zn, Sr, B, Y, Sn, Al, Nb, Ti, Zr, W, Sr, Co, and Mo.
[0048] The chemical formula of this sodium-based layered oxide cathode material reveals that it is composed of elements such as sodium, nickel, iron, manganese, and M. Here, x, a, b, c, and d are the molar ratios of each element, satisfying the sum condition: (a+b+c+d) = 1. Adjusting the value of x alters the sodium ion insertion / extraction capability, while adjusting the ratio of Ni, Fe, and Mn balances the material's energy density and stability. The introduction of dopant element M further optimizes the material's crystal structure, thereby improving its cycle stability.
[0049] In some embodiments, the average particle size Dv50 of the cathode material is 6 μm to 15 μm. Dv50 describes the particle size distribution of the material; it represents the particle size value when the total particle count in a sample reaches 50%. Typically, it refers to a 50% proportion of powder particles larger and 50% smaller than this particle size. As an example, the Dv50 particle size of the cathode material can be typical but not limiting values such as 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 12 μm, 14 μm, and 15 μm. The particle size of the cathode material has a significant impact on battery performance. The cathode material of this application has a suitable particle size range, which can better improve the energy density and power density of sodium-ion batteries, thereby improving the cycle life of the battery.
[0050] This invention also proposes a method for preparing a positive electrode material, comprising the following steps:
[0051] A metal salt solution containing nickel, iron, and manganese sources is prepared. The metal salt solution is then subjected to a co-precipitation reaction to obtain a precursor. The precursor is mixed with sodium and M sources and subjected to a first calcination treatment to obtain a cathode material precursor. The cathode material precursor is then combined with M... 1 The source material is mixed and then subjected to a second calcination process to obtain the cathode material.
[0052] In other embodiments, a method for preparing a cathode material is also proposed, comprising the following steps:
[0053] A metal salt solution containing nickel, iron, manganese, and M sources was prepared. The metal salt solution was then subjected to a co-precipitation reaction to obtain a precursor. The precursor was mixed with a sodium source and subjected to a first sintering treatment to obtain a cathode material precursor. The cathode material precursor was then combined with M... 1 The source is mixed and then subjected to a second sintering process to obtain the cathode material.
[0054] In the embodiments of this application, the nickel source, manganese source, and iron source are each independently selected from any one or more combinations of sulfates, hydrochlorides, nitrates, carbonates, acetates, oxides, sulfides, nitrides, and hydroxides of the corresponding metal ions. The sodium source includes any one or more combinations of anhydrous sodium carbonate, sodium carbonate monohydrate, sodium carbonate decahydrate, sodium bicarbonate, and sodium sulfate. Mixing can be performed using mixing equipment such as a mixer, high-speed mixer, or ball mill.
[0055] In the two methods for preparing the cathode material described above, the M source includes at least one of the following: K source, Li source, Ca source, Cu source, Mg source, Zn source, Sr source, B source, Y source, Sn source, Al source, Nb source, Ti source, Zr source, W source, Sr source, Co source, and Mo source. As an example, the M source is selected from any one or more combinations of sulfates, hydrochlorides, nitrates, carbonates, acetates, oxides, sulfides, nitrides, or hydroxides corresponding to K, Li, Ca, Cu, Mg, Zn, Sr, B, Y, Sn, Al, Nb, Ti, Zr, W, Sr, Co, and Mo.
[0056] M 1 The source includes at least one of Cu, B, Nb, W, Ti, and Ca sources. Cu, B, Nb, W, Ti, and Ca source elements have strong fluxing ability and moderate chemical activity, making them more suitable for achieving uneven fluxing effects.
[0057] M 1 The particle size distribution of the source is 2≤(D90-D10) / D50≤10. The particle size distribution parameters (D10, D50, D90) are key indicators in the statistical analysis of material particle size. Specifically, D10 represents the particle size of 10% of the particles in the cumulative particle size distribution curve that is smaller than this value; D50 represents the particle size of 50% of the particles in the cumulative particle size distribution curve that is smaller than this value (i.e., the median particle size); and D90 represents the particle size of 90% of the particles in the cumulative particle size distribution curve that is smaller than this value.
[0058] (D90-D10) / D50 is a dimensionless ratio used to measure the width or uniformity of particle size distribution. Here, (D90-D10) represents the span of the particle size distribution, that is, the range of particle sizes covered by 10% to 90% of the particles. Therefore, the smaller (D90-D10) / D50 is, the more concentrated the particle size distribution; conversely, the larger the value, the wider the particle size distribution. A range of 2 ≤ (D90-D10) / D50 ≤ 10 indicates that the particle size distribution is neither too concentrated (e.g., close to monodispersity) nor too wide (e.g., multimodal distribution), but rather within a moderate range.
[0059] M 1 The source particle size parameters are 0.1μm≤D10≤2μm, 10μm≤D90≤100μm, and 0.8μm≤D50≤10μm. This particle size parameter range represents M. 1 The upper limit of small particles in the source powder is ≤2μm, M 1 The lower limit for large particles in the source powder is ≥10μm, which means M 1The source powder exhibits a wide particle size distribution, ranging from very fine (≤2μm) to relatively large (≥10μm). Fine particles are more easily dispersed on the surface of the cathode material precursor, forming localized high-concentration regions. Due to their smaller size, they can penetrate deeper into the micropores or defects on the particle surface, resulting in a stronger fluxing effect at these locations, leading to intense melting and grain growth, forming larger, plate-like particles. Larger particles, however, are more difficult to disperse uniformly and tend to concentrate in certain areas. Their presence results in lower local melting levels and retains smaller agglomerates. This leads to an uneven fluxing effect on the cathode material particle surface. Therefore, M 1 The wide particle size distribution of the source powder leads to uneven distribution and effect of the flux on the surface of the cathode material particles, thus achieving the effect of simultaneously forming large plate-like particles and small agglomerate particles in the same particle during the sintering process.
[0060] The cathode material of this invention can be prepared by co-precipitation followed by a high-temperature solid-state method. The cathode material Na designed according to this application... x Ni a Fe b Mn c M d Based on the atomic ratio of O2, calculate the appropriate molar ratios of Na, Ni, Fe, Mn, and M, then convert this to the masses of Na, Ni, Fe, Mn, and M sources, and weigh the corresponding masses of material. First, using Ni, Fe, and Mn sources as raw materials, prepare a nickel-manganese-iron ternary precursor using a co-precipitation method. Alternatively, use Ni, Fe, Mn, and M sources as raw materials and prepare a precursor containing Ni, Fe, Mn, and M using a co-precipitation method. The co-precipitation method can employ existing techniques and will not be elaborated here. Then, mix the nickel-manganese-iron ternary precursor with sodium and M sources, or mix the precursor containing Ni, Fe, Mn, and M with a sodium source, and then co-sinter to bond the precursor material particles together to form the cathode material precursor. Then, during a second sintering process, add M with a wide particle size distribution to the cathode material precursor. 1 Using source powder as a flux, a non-uniform fluxing effect is achieved on the particle surface. This method can simultaneously form large, plate-like particles and smaller, aggregated particles within the same particle. The preparation process is simple and easy to implement, making it highly suitable for large-scale industrial production.
[0061] In some implementations, M 1The mass ratio of the source to the cathode material precursor is 1:(20-200). For example, typical but not limiting values include 1:20, 1:50, 1:80, 1:120, 1:140, 1:170, and 1:200. Maintaining a mass ratio within these ranges can result in a cathode material with better performance.
[0062] In some embodiments, the molar ratio of sodium in the sodium source to nickel in the nickel source, iron in the iron source, manganese in the manganese source, and M in the M source is (0.6-1):(0.1-0.4):(0.1-0.4):(0.2-0.8):(0.01-0.2).
[0063] In some embodiments, the first sintering treatment lasts for 3 to 12 hours, and the calcination temperature is 800°C to 950°C. In some embodiments, the second sintering treatment lasts for 6 to 15 hours, and the calcination temperature is 850°C to 1000°C. As examples, the first calcination temperature can be typical but not limiting values such as 800°C, 850°C, 870°C, 900°C, 920°C, 940°C, and 950°C; the second calcination temperature can be typical but not limiting values such as 850°C, 870°C, 900°C, 920°C, 940°C, 960°C, 980°C, and 1000°C. The first calcination time can be typical but not limiting values such as 3 hours, 6 hours, 7 hours, 8 hours, 9 hours, 11 hours, and 12 hours. The second calcination time can be typical but not limiting values such as 6 hours, 7 hours, 8 hours, 9 hours, 11 hours, 13 hours, and 15 hours. The sintering process in this embodiment can be carried out in an inert gas atmosphere. The inert gas includes, but is not limited to, at least one of nitrogen, argon, and helium. For example, argon can be selected as the inert gas, and the gas flow rate can be 5 L / min. The sintering temperature has a significant impact on the structure and electrochemical performance of the cathode material. If the sintering temperature is too low, a cathode material with a "roujiamo" (Chinese hamburger) morphology cannot be prepared; if the sintering temperature is too high, the stability and cycle life of the cathode material may decrease. By controlling the sintering temperature within the above-mentioned range, a cathode material with the structural characteristics of this invention and good electrochemical performance can be prepared.
[0064] On the other hand, embodiments of the present invention also provide a positive electrode sheet, including a current collector and a positive electrode active material layer disposed on at least one surface of the current collector, wherein the positive electrode active material layer includes the above-mentioned positive electrode material or a positive electrode material prepared by the above-mentioned preparation method.
[0065] On the other hand, embodiments of the present invention also propose a sodium-ion battery, which includes the above-mentioned positive electrode sheet.
[0066] The following description is based on specific embodiments.
[0067] Example 1
[0068] This embodiment provides a positive electrode material with the chemical formula Na. 0.7 Ni 0.2 Fe 0.2 Mn 0.4 Cu 0.2 O2. The preparation method of this cathode material includes the following steps:
[0069] S1: A near-spherical hydroxide precursor with Ni:Fe:Mn = 1:1:2 was prepared by co-precipitation method;
[0070] S2: Weigh the sample containing the precursor, sodium carbonate, and copper oxide in a molar ratio of Na:Ni:Fe:Mn:Cu of 0.7:0.2:0.2:0.4:0.2 as raw material. Mix half the weight of copper oxide with the precursor and sodium carbonate in a planetary ball mill, then place it in a box furnace for sintering at 830℃ for 8 hours. After naturally cooling to room temperature, crush the mixture to obtain the cathode material precursor.
[0071] S3: The cathode material precursor was mixed with the remaining half-weight of copper oxide (particle size parameters D10 = 0.8 μm, D50 = 2.5 μm, D90 = 15.6 μm), and then heated to 900℃ for sintering for 12 hours for the second stage of sintering. Finally, it was allowed to cool naturally to obtain a cathode material with a roujiamo (Chinese hamburger) morphology (see...). Figure 1 ).
[0072] Example 2
[0073] This embodiment provides a positive electrode material with the chemical formula Na. 0.8 Ni 0.15 Fe 0.3 Mn 0.45 Cu 0.1 O2. The preparation method of this cathode material includes the following steps:
[0074] S1: A spherical hydroxide precursor with Ni:Fe:Mn = 1:2:3 was prepared by co-precipitation method;
[0075] S2: Weigh the sample as raw material using the precursor, sodium carbonate, and copper oxide in a molar ratio of Na:Ni:Fe:Mn:Cu of 0.8:0.15:0.3:0.45:0.1. Mix half the weight of copper oxide with the precursor and sodium carbonate in a planetary ball mill, then place the mixture in a box furnace for sintering at 850℃ for 8 hours. After natural cooling to room temperature, crush the mixture to obtain the cathode material precursor.
[0076] S3: Add the remaining half weight of copper oxide (particle size parameters D10 = 0.8 μm, D50 = 2.5 μm, D90 = 15.6 μm) to the cathode material precursor, mix again, heat to 900℃ and sinter for 8 hours for the second stage of sintering, and finally cool naturally to obtain a cathode material with the morphology of a roujiamo (Chinese hamburger).
[0077] Example 3
[0078] This embodiment provides a positive electrode material with the chemical formula Na. 0.75 Ni 0.24 Fe 0.24 Mn 0.36 Zn 0.1 Nb 0.06 O2. The preparation method of this cathode material includes the following steps:
[0079] S1: A spherical hydroxide precursor with Ni:Fe:Mn = 2:2:3 was prepared by co-precipitation method;
[0080] S2: The precursor, sodium carbonate, zinc oxide, and niobium oxide were weighed as raw materials according to a molar ratio of Na:Ni:Fe:Mn:Zn:Nb of 0.75:0.24:0.24:0.36:0.1:0.06. The precursor, sodium carbonate, and zinc oxide were mixed evenly in a planetary ball mill, and then placed in a box furnace for sintering. The mixture was held at 900℃ for 6 hours, and then naturally cooled to room temperature before being crushed to obtain the cathode material precursor.
[0081] S3: Niobium oxide (particle size parameters D10 = 0.4 μm, D50 = 1.3 μm, D90 = 9.9 μm) was added to the cathode material precursor and remixed. The mixture was then heated to 950℃ and sintered for 14 h for the second stage of sintering. Finally, the mixture was allowed to cool naturally to obtain a cathode material with a roujiamo (Chinese hamburger) morphology.
[0082] Example 4
[0083] This embodiment provides a positive electrode material with the chemical formula Na. 0.9 Ni 0.2 Fe 0.2 Mn 0.5 Ca 0.05 Nb 0.05 O2. The preparation method of this cathode material includes the following steps:
[0084] S1: A near-spherical hydroxide precursor with Ni:Fe:Mn:Ca = 2:2:5:0.5 was prepared by co-precipitation method;
[0085] S2: The precursor, sodium carbonate, and niobium oxide were weighed as raw materials according to a molar ratio of Na:Ni:Fe:Mn:Ca:Nb of 0.9:0.2:0.2:0.5:0.05:0.05. The precursor and sodium carbonate were mixed evenly in a planetary ball mill, and then sintered in a box furnace at 900℃ for 6 hours. After natural cooling to room temperature, the mixture was crushed to obtain the cathode material precursor.
[0086] S3: Niobium oxide (particle size parameters D10 = 0.4 μm, D50 = 1.3 μm, D90 = 9.9 μm) was added to the cathode material precursor and remixed. The mixture was then heated to 950℃ and sintered for 14 h for the second stage of sintering. Finally, the mixture was allowed to cool naturally to obtain a cathode material with a roujiamo (Chinese hamburger) morphology.
[0087] Example 5
[0088] This embodiment provides a positive electrode material with the chemical formula Na. 0.9 Ni 0.2 Fe 0.2 Mn 0.4 Ti 0.1 Cu 0.08 Nb 0.02 O2. The preparation method of this cathode material includes the following steps:
[0089] S1: A near-spherical hydroxide precursor with Ni:Fe:Mn:Ti:Cu = 2:2:4:1:0.8 was prepared by co-precipitation method;
[0090] S2: The precursor, sodium carbonate, and niobium oxide were weighed as raw materials according to the molar ratio of Na:Ni:Fe:Mn:Ti:Cu of 0.9:0.2:0.2:0.4:0.08:0.02. The precursor and sodium carbonate were mixed evenly in a planetary ball mill, and then sintered in a box furnace at 900℃ for 10 hours. After natural cooling to room temperature, the mixture was crushed to obtain the cathode material precursor.
[0091] S3: Niobium oxide (particle size parameters D10 = 0.4 μm, D50 = 1.3 μm, D90 = 9.9 μm) was added to the cathode material precursor and remixed. The mixture was then heated to 950℃ and sintered for 12 h for the second stage of sintering. Finally, the mixture was allowed to cool naturally to obtain a cathode material with a roujiamo (Chinese hamburger) morphology.
[0092] Example 6
[0093] This embodiment provides a positive electrode material with the chemical formula Na. 0.9 Ni 0.33 Fe 0.33 Mn 0.33 Cu 0.01O2. The preparation method of this cathode material includes the following steps:
[0094] S1: A near-spherical hydroxide precursor with Ni:Fe:Mn = 0.33:0.33:0.33 was prepared by co-precipitation method;
[0095] S2: Weigh the sample containing the precursor, sodium carbonate, and titanium oxide in a molar ratio of Na:Ni:Fe:Mn of 0.9:0.33:0.33:0.33 as raw material. Mix the precursor and sodium carbonate evenly in a planetary ball mill, then place it in a box furnace for sintering at 900℃ for 10 hours. After naturally cooling to room temperature, crush the mixture to obtain the cathode material precursor.
[0096] S3: Add copper oxide (particle size parameters D10 = 0.8 μm, D50 = 2.5 μm, D90 = 15.6 μm) to the cathode material precursor, remix, heat to 950℃ and sinter for 12 hours for the second stage of sintering, and finally cool naturally to obtain a cathode material with the morphology of a roujiamo (Chinese hamburger).
[0097] Comparative Example 1
[0098] The difference between the preparation method of the cathode material in Comparative Example 1 and Example 1 is that M is added in the second stage of sintering. 1 The particle size of the source (copper oxide) satisfies the particle size parameters D10 = 1.5 μm, D50 = 3.9 μm, and D90 = 7.6 μm.
[0099] The cathode material in Comparative Example 1 did not exhibit a distinctive meat-filled bun morphology; this was primarily due to the addition of M. 1 The source particles are relatively uniform in size, and their fusing effect results in small differences in the primary particle size of the sample, making it impossible to form a special roujiamo (Chinese hamburger) morphology, such as... Figure 2 As shown, the cathode material is formed by the direct stacking of primary particles of similar size, with no obvious layering or encapsulation between the particles.
[0100] Comparative Example 2
[0101] The difference between the preparation method of the cathode material in Comparative Example 2 and Example 2 is that M is added during the second stage of sintering. 1 The particle size of the source (copper oxide) satisfies the particle size parameters D10 = 0.7 μm, D50 = 10.5 μm, and D90 = 112.2 μm.
[0102] The cathode material in Comparative Example 2 did not exhibit a distinctive meat-and-bun morphology and clearly contained unreacted M1 sources. This was primarily due to the addition of M... 1 The source particle size distribution was too uneven and the D90 was too large, resulting in insufficient sintering and an inability to form a uniformly composed finished material and the desired morphology for the roujiamo (Chinese hamburger). Figure 3As shown, the cathode material has irregular particles with obvious unsintered raw material particles.
[0103] Comparative Example 3
[0104] The difference between the preparation method of the cathode material in Comparative Example 3 and Example 3 is that zinc oxide is added as a flux in the second sintering stage.
[0105] The cathode material in Comparative Example 3 did not exhibit a distinctive "meat sandwich" morphology. This was primarily due to the poor fluxing effect of zinc oxide, which prevented the formation of the characteristic morphology. Figure 4 As shown, all the particles of this cathode material have similar particle sizes and do not form a structure of "small particle core and large particle outer layer".
[0106] Comparative Example 4
[0107] The difference between the preparation method of the cathode material in Comparative Example 4 and Example 4 is that the second sintering stage did not include the M mentioned in this invention. 1 The source is used as a fluxing agent. In step one, a spherical hydroxide precursor with Ni:Fe:Mn:Ca = 2:2:5:1 is prepared by co-precipitation.
[0108] The cathode material in Comparative Example 4 did not exhibit the characteristic meat-and-bun morphology, primarily due to the absence of M. 1 The source, acting as a fluxing agent, prevented the sample from forming a unique roujiamo (Chinese hamburger) morphology.
[0109] Comparative Example 5
[0110] The preparation method of the cathode material in Comparative Example 5 differs from that in Example 5 in that sodium carbonate, ferric oxide, manganese oxide, titanium oxide, and copper oxide were weighed and used as raw materials in a Na:Ni:Fe:Mn:Ti:Cu ratio of 0.9:0.2:0.2:0.4:0.1:0.1 for both the first and second stage sintering. The spherical hydroxide precursor with a Ni:Fe:Mn:Ti:Cu ratio of 2:2:4:1:1 prepared by the co-precipitation method was not used. The cathode material in Comparative Example 5 did not exhibit a distinctive "meat sandwich" morphology, primarily because the cathode material formed by sintering pure oxides has a poor morphology and cannot form the characteristic "meat sandwich" shape.
[0111] Material property testing
[0112] To verify the progressiveness of the embodiments of this application, the samples of the embodiments and comparative examples were subjected to the following tests:
[0113] 1. Scanning electron microscope (SEM)
[0114] Scanning electron microscopy (SEM) uses an electron beam to scan the sample surface to obtain information about the material's surface morphology. When the electron beam bombards the sample surface, the interaction between the electron beam and the material generates secondary and scattered electrons, which, through further processing, become the corresponding morphological image. SEM resolution is approximately 2 nm. Through SEM testing, in-depth and detailed analysis of the microstructure and structure of materials can be performed, and the morphology of cathode materials can be characterized. This application uses a Hitachi S-4800 scanning electron microscope (SEM) to characterize the material morphology.
[0115] 2. Average particle size D V 50 tests
[0116] Equipment model: Malvern 3000 (MasterSizer 2000) laser particle size analyzer; Reference standard procedure: GB / T19077-2016 / ISO 13320:2009; Specific test procedure: Take an appropriate amount of the sample to be tested (the sample concentration should be 8-12% opacity), add 20ml NMP, and simultaneously incubate for 5 minutes (53KHz / 120W) to ensure complete dispersion of the sample. Then, measure the sample according to the GB / T19077-2016 / ISO 13320:2009 standard.
[0117] 3. Specific surface area test
[0118] After the sintered material cools to room temperature, it is sieved using a vibrating screen with a mesh size of 300. The vibrating screen is started, and after sieving, it is turned off. Large, flaky primary particles remain on the screen, while smaller primary particles pass through, indicating successful sieving. The two materials are then collected and their specific surface area is measured using a Micromeritics 3030 instrument employing nitrogen adsorption based on the Brunauer-Emmett-Teller (BET) theory. The specific surface area parameters of the two materials are then obtained.
[0119] 4. Elemental analysis test
[0120] The Na and metal element content in the cathode material was determined using an inductively coupled plasma atomic absorption spectrometer (ICP, instrument model: PE Optima 7000DV). First, an appropriate amount of powder sample was weighed, and approximately 10 mL of aqua regia was added. The sample was heated at approximately 185°C for 30 to 50 minutes to ensure complete digestion before being tested.
[0121] 5. Positive electrode thickness test
[0122] Using a digital micrometer or thickness gauge with an accuracy of 1 μm, select at least 5 evenly distributed measurement points on the electrode surface (avoiding edges and areas with uneven coating), and gently apply standard pressure (usually 20-50 g / cm2) to ensure flat contact; record the thickness value of each measurement point, and calculate the average value as the electrode thickness. The test must be carried out in a constant temperature and humidity environment (e.g., temperature 23℃±2℃, humidity 50%±5%).
[0123] Battery performance test
[0124] The positive electrode material prepared in the above examples and comparative examples was mixed with a conductive agent (conductive carbon black) and a binder, polyvinylidene fluoride (PVDF), in a weight ratio of 90:5:5 and uniformly coated onto aluminum foil to form an electrode sheet, which was then vacuum dried. 12.5% sodium NaPF6 was dissolved in diethylene glycol dimethyl ether (DIGLYME) and stirred until homogeneous to serve as the electrolyte. CR2032 coin cells were assembled and tested in an argon atmosphere glove box (H2O < 0.1 ppm, O2 < 0.1 ppm).
[0125] 1. Specific capacity test
[0126] The battery was charged and discharged at a rate of 0.1C within a voltage range of 2.0V to 4.0V. Then, the battery was charged to 4.0V under constant current conditions and maintained at constant voltage until the current decayed to 0.05C. Subsequently, it was discharged from 4.0V to 2.0V at the same rate, and the discharge capacity Q (in mAh) was recorded throughout the process. At the same time, the mass m (in g) of the active material in the battery was measured, and the specific capacity (in mAh / g) was calculated using the formula specific capacity = Q / m.
[0127] 2. Battery capacity retention test
[0128] The battery capacity retention rate test process is as follows: At 25°C, the battery is charged to 4.8V at a constant current density of 20mA / g, and then discharged to 2.0V at a constant current density of 20mA / g, obtaining the discharge specific capacity C0 of the coin cell. Subsequently, it undergoes 100 cycles of constant current charge-discharge at 20mA / g, and the discharge specific capacity C1 of the 100th cycle is taken. The capacity retention rate of the positive electrode active material after 100 cycles = (C1 / C0) × 100%. The battery capacity retention rate data corresponding to Example 1 in Table 1 are the data measured after 100 cycles under the above test conditions. The test process for the comparative example and other examples is the same as above.
[0129] 3.10C / 1C Capacity Retention Test
[0130] Discharge the battery at a constant current rate of 1C to the termination voltage of 2.5V, and record the discharge capacity Q. 1CThen recharge the battery, and then discharge it at a constant current rate of 10C until the same termination voltage of 2.5V is reached. Record the discharge capacity Q. 10C Finally, according to the formula:
[0131] Capacity retention rate = Q 10C / Q 1C The capacity retention rate is calculated by multiplying by 100% to evaluate the battery's performance under high-rate conditions.
[0132] Performance Results
[0133] Figure 1 The image shows the SEM morphology of the cathode material in Example 1. As can be seen from the image, a single secondary particle of the cathode material is composed of several larger sheet-like primary particles and multiple smaller particle agglomerates. The small particle agglomerates are clustered between the larger sheet-like particles, forming a unique "meat sandwich" morphology.
[0134] Tables 1 and 2 present the characterization data of the cathode materials obtained in Examples 1-5 and Comparative Examples 1-5. Note that Comparative Examples 1-5 did not exhibit the unique "meat sandwich" morphology. Figures 2 to 4 The samples did not distinguish between several large, plate-like primary particles and numerous small particles, and did not contain the specific surface area S1 or S2, average length L, average width W, and average particle size R defined in this application. Therefore, the average specific surface area, average length, average width, and average particle size of the cathode materials obtained in Comparative Examples 1-5 were not further measured.
[0135] Table 1
[0136]
[0137] Table 2
[0138]
[0139] As shown in Table 2, the specific capacity of the embodiments is generally higher than or equal to that of the comparative examples. For example, the specific capacity of Embodiment 1 is 123 mAh / g, while that of Comparative Example 1 is only 115 mAh / g. This indicates that the embodiments have higher energy density.
[0140] The capacity retention of the embodiments is significantly better than that of the comparative examples. For example, the 100th-cycle capacity retention of Embodiment 1 is 96.3%, while that of Comparative Example 1 is only 88.2%. Compared with the comparative examples, the embodiments perform better in cycle life (100th-cycle capacity retention), demonstrating better stability and durability.
[0141] The electrode thickness of the embodiments showed minimal change after 100 charge-discharge cycles, indicating good structural stability. For example, the initial thickness of Embodiment 1 was 0.197 mm, and after 100 charge-discharge cycles it was 0.199 mm, a very small change; while the initial thickness of Comparative Example 1 was 0.189 mm, and after 100 charge-discharge cycles it was 0.204 mm, a larger change. These results show that, compared to the comparative example, the embodiments exhibit greater structural stability and are less prone to expansion during multiple charge-discharge cycles.
[0142] The above description is merely an exemplary embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural transformations made using the contents of the present invention specification and drawings under the technical concept of the present invention, or direct / indirect applications in other related technical fields, are included within the patent protection scope of the present invention.
Claims
1. A method for preparing a positive electrode material, characterized in that, Includes the following steps: A metal salt solution containing nickel, iron, and manganese sources was prepared, and the metal salt solution was subjected to a co-precipitation reaction to obtain a precursor; the precursor was then reacted with a sodium source and a manganese source. 2 After mixing the source materials, a first calcination treatment is performed to obtain a cathode material precursor; the cathode material precursor is then mixed with M... 1 The source is mixed and then subjected to a second calcination treatment to obtain the cathode material; Alternatively, configure a source containing nickel, iron, manganese, and M. 2 A metal salt solution from a source is used to obtain a precursor through a co-precipitation reaction. The precursor is then mixed with a sodium source and subjected to a first sintering treatment to obtain a cathode material precursor. The cathode material precursor is then combined with M... 1 After mixing the source materials, a second sintering process is performed to obtain the cathode material. Wherein, source M includes the M 2 Source and the M 1 Source, the M 2 The source includes at least one of the following: K source, Li source, Ca source, Cu source, Mg source, Zn source, Sr source, B source, Y source, Sn source, Al source, Nb source, Ti source, Zr source, W source, Sr source, Co source, and Mo source. The M 1 The source includes at least one of Cu, B, Nb, W, Ti, and Ca sources; the M 1 The particle size distribution of the source is 2≤(D90-D10) / D50≤10; The M 1 The particle size parameters of the source are 0.1μm≤D10≤2μm, 10μm≤D90≤100μm, and 0.8μm≤D50≤10μm; The M 1 The mass ratio of the source to the cathode material precursor is 1:(20~200).
2. The method for preparing the cathode material as described in claim 1, characterized in that, The molar ratio of sodium in the sodium source, nickel in the nickel source, iron in the iron source, manganese in the manganese source, and M in the M source is (0.6~1):(0.1~0.4):(0.1~0.4):(0.2~0.8):(0.01~0.2). Wherein, the molar amount of element M in the M source is the M 1 M in the source 1 The molar amount of the element and the M 2 M in the source 2 The sum of the molar amounts of the elements.
3. The method for preparing the cathode material as described in claim 1 or 2, characterized in that, The first sintering treatment lasts for 3 to 12 hours, and the calcination temperature is 800°C to 950°C. The second sintering treatment takes 6 to 15 hours and the calcination temperature is 850°C to 1000°C.
4. A positive electrode material, prepared by any one of claims 1 to 3.
5. The positive electrode material as described in claim 4, characterized in that, The cathode material is a sodium-based crystalline oxide, comprising an outer coating layer and a core aggregate, wherein the core aggregate is embedded within the outer coating layer and the outer coating layer at least partially covers the core aggregate; The outer wrapping layer is formed by stacking sheet-like primary particles, and the core aggregate is formed by interweaving and agglomerating granular primary particles.
6. The cathode material as described in claim 5, characterized in that, The average length L of the plate-like primary particles is 1.5μm to 10μm, and the average width W is 0.5μm to 8μm; the average particle size R of the granular primary particles is 0.1μm to 2μm.
7. The cathode material according to any one of claims 4 to 6, characterized in that, The chemical formula of the positive electrode material is Na. x Ni a Fe b Mn c M d O2, wherein (a+b+c+d)=1, 0.6≤x≤1.0, 0.1≤a≤0.4, 0.1≤b≤0.4, 0.2≤c≤0.8, 0.01≤d≤0.2; M includes at least one element selected from K, Li, Ca, Cu, Mg, Zn, Sr, B, Y, Sn, Al, Nb, Ti, Zr, W, Sr, Co, and Mo; Wherein, the M element includes the M 1 M in the source 1 Element and the M 2 M in the source 2 element.
8. The cathode material according to any one of claims 4 to 6, characterized in that, The average particle size Dv50 of the cathode material is 6 μm to 15 μm.
9. A positive electrode sheet, characterized in that, The present invention includes a current collector and a positive electrode active material layer disposed on at least one surface of the current collector, wherein the positive electrode active material layer comprises the positive electrode material according to any one of claims 4 to 8 or the positive electrode material prepared by any one of claims 1 to 3.
10. A sodium-ion battery, characterized in that, The sodium-ion battery includes the positive electrode sheet as described in claim 9.
Citation Information
Patent Citations
Positive electrode active material for lithium secondary battery, method for preparing same, and lithium secondary battery comprising same
CN117916913A
High-capacity sodium battery positive electrode material, preparation method thereof, positive plate and sodium ion battery
CN118572083A